Valor adicionado pelo comércio intra e internacional: uma análise do estado de São Paulo - Almeida, Danielly Loureiro (2022)
The aim of this research is to identify the share of domestic value added in the state of São Paulo that is embedded in exports to other Federation Units and to other countries, as well as to determine the share of value added from other states linked to sales to São Paulo, for the years 2008 and 2013. For this, the input-output analysis was used as a methodology, specifically an adaptation of the hypothetical extraction technique proposed by Los, Timmer and De Vries (2016). The results show that, in the analyzed period, São Paulo has relatively increased its independence in relation to the other FUs, both in intranational commercialization and in the products acquired from the other FUs for their international exports. Like most FUs, to a certain extent, they are also becoming less dependent on São Paulo, at least in terms of intranational trade. It can be concluded that, in general, the national economy became relatively less centralized in the state of São Paulo. This decentralization may have occurred in two ways: (a) by increasing commercial relations between the other FUs to the detriment of São Paulo and/or by strengthening the domestic market of the UFs themselves, increasing the percentage of added value produced internally. This strengthening of the domestic market may be linked to the increased participation of the service sectors, both in the São Paulo economy and in the Brazilian economy as a whole. With regard to international trade, São Paulo appears as the largest exporter among the FUs, in terms of the total value exported. However, it was found that about twenty percent of the added value linked to São Paulo exports was generated in other FUs, due to the fact that São Paulo acquires inputs in these FUs to compose its products for export. This percentage decreased between 2008 and 2013, indicating that SP appears to be moving towards expanding the acquisition of inputs within the state itself.